COMPARATIVE GENOMICS AND EXPRESSION ANALYSIS OF KCS GENES UNDER DROUGHT STRESS IN SUNFLOWER (HELIANTHUS ANNUUS L.) - P. Zaib; T. Shaheen; M. Hamyat; Mahmood-ur-Rahman (Journal of Animal and Plant Sciences, 2022)
Water stress is considered as the main environmental factor which badly affects growth of sunflower plant. It is a water sensitive plant whose yield is greatly affected by drought stress. Several studies have been done to understand the mechanism of drought stress tolerance in plants, and exploring the role of stress tolerant genes is one of them. KCS genes, responsible for wax biosynthesis, have been reported to be involved in drought stress tolerance mechanism. In this study, expression profiling of KCS genes was done to understand their role in stress mechanism. Comparative genomics studies of KCS genes were carried out in sunflower and Arabidopsis by constructing phylogenetic tree. They were divided into six clades, however they were present in the same clade showing similarities between Arabidopsis and sunflower. It was further confirmed by Synteny analysis and concluded that KCS genes in both species share the same evolutionary origin. Further, they were amplified in sunflower by using gene specific primers. Five genes, i.e. KCS2, KCS4, KCS5, KCS10 and KCS18were successfully amplified in sunflower variety FH-593. Then, sunflower plants were subjected to drought stress and expression profiling of amplified KCS genes was carried out by Real Time PCR. All the five genes were up-regulated under drought showing their role in stress conditions; however, the expression level of each gene was varied. Maximum relative expression was found for KCS4 gene in T1, i.e. 19 fold as compared to control. The expression of other genes was found in decreasing order as indicated KCS4>KCS2>KCS5>KCS10>KCS18 (relative expression: 19, 12, 5, 4 and 3 respectively). Biochemical analyses were also performed and significant variation was found among treatments and control. Total chlorophyll contents were decreased under drought stress while antioxidants like catalase, peroxidase, superoxide dismutase and proline were increased. Our results showed the role of KCS genes in drought stress which is first ever report in sunflower. This study concluded that KCS genes have role in drought stress tolerance and their expression is significantly up-regulated under stress conditions. The information presented here may help to further characterize KCS genes and their subsequent use to engineer drought stress in crop plants.
Keywords: Sunflower; wax biosynthesis; drought; gene expression profiling; KCS genes